Aero-acoustic analysis with a permeable surface for Tip-jet rotor noise characteristics in hovering flight - Kim, K.; Park, M.J.; Park, D.; Park, S.H.; Lee, D.J. (My University, 2018)
This paper presents aero-acoustics in far-field computed by an acoustic analogy code using numerical permeable surfaces for the Tip-jet 80-inch model rotor blade in hovering flight. A chimera grid method is applied to the present simulation to consider the blade motion and moving effects. The permeable surface covering the blade and jet flow is constructed to include the thickness noise, loading noise and the flow noise generated from the shock waves, tip vortices and ejected jet. The Kirchhoff approach is applied to Ffowcs Williams and Hawkings (FW-H) equations to efficient noise prediction in far-field. High speed impulsive noise due to blade tip shock waves and jet flow with large pressure gradient is predicted. Noise characteristics in far-field are investigated with jet flow parameters such as duct inlet pressure and total pressure.